Comparison of linear measurements and analyses taken from plaster models and three-dimensional images - Porto, Betina Grehs [UNESP]; Porto, Thiago Soares [UNESP]; Silva, Monica Barros; Grehs, Renésio Armindo; Pinto, Ary dos Santos [UNESP]; Bhandi, Shilpa H.; Tonetto, Mateus Rodrigues; Bandéca, Matheus Coelho; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP] (Jaypee Brothers Medical Publishing, 2014)
Digital models are an alternative for carrying out analyses and devising treatment plans in orthodontics. The objective of this study was to evaluate the accuracy and the reproducibility of measurements of tooth sizes, interdental distances and analyses of occlusion using plaster models and their digital images. Thirty pairs of plaster models were chosen at random, and the digital images of each plaster model were obtained using a laser scanner (3Shape R-700, 3Shape A/S). With the plaster models, the measurements were taken using a caliper (Mitutoyo Digimatic(®), Mitutoyo (UK) Ltd) and the MicroScribe (MS) 3DX (Immersion, San Jose, Calif). For the digital images, the measurement tools used were those from the O3d software (Widialabs, Brazil). The data obtained were compared statistically using the Dahlberg formula, analysis of variance and the Tukey test (p < 0.05). The majority of the measurements, obtained using the caliper and O3d were identical, and both were significantly different from those obtained using the MS. Intra-examiner agreement was lowest when using the MS. The results demonstrated that the accuracy and reproducibility of the tooth measurements and analyses from the plaster models using the caliper and from the digital models using O3d software were identical.
Keywords: Digital models; Study models; Orthodontics